THE ROLE OF FAMILY COMMUNICATION PATTERN AS A MEDIATOR IN THE RELATIONSHIP BETWEEN SOCIAL SUPPORT PERCEPTIONS AND PSYCHOLOGICAL WELFARE OF FEMALE ELEMENTARY TEACHERS DURING THE COVID-19 PANDEMIC - Noori Lukman Pradipto; Frieda M. Mangunsong S (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The Covid-19 pandemic presents many new challenges for teachers, especially female teachers who teach at the elementary level. It was assumed that communication between family members helped teachers through difficult times during the Covid-19 pandemic. This research was conducted to observe the role of family communication patterns, both in the conversation and conformity dimensions, as a mediator in the relationship between social support perceptions and psychological welfare of female elementary school teachers. The results showed that there was a significant relationship between social support perceptions and psychological welfare, both directly (β = 0.57, t (117) = 7.91, p = 0.000) and indirectly through the conversation dimension of family communication pattern (coefficient = 0.42, SE = 0.07, CI = 0.27–0.56). On the other hand, family communication patterns emphasizing conformity in belief did not act as a mediator because they did not show a significant relationship with psychological welfare (coefficient = -0.11, SE = 0.10, CI = -0.32–0.10, p = 0.300). The results implied that social support from various sources was needed by teachers in facing the pandemic situation in order to be happy, regardless of communication patterns at home.